Testing the Environmental Kuznets Curve Hypothesis within the Context of Industrial Development through NARDL Model: The Case of France - Artekin, Ayşe Özge (International Journal of Energy Economics and Policy, 2024)
Energy is one of the necessary and vital factors for the economic development of countries and the increase in living standards. The limited availability of conventional energy resources, in parallel with the rapid increase in energy consumption due to industrialization activities and technological developments, has encouraged countries to change their energy production policies and use alternative energy sources. For this purpose, in the study, the relationship and direction of the relationship between industrial production, CO2 emissions, energy use and economic growth in France are examined with the carrying out of the ADF, PP, KPSS unit root and the NARDL test for the period 1990–2023. The analysis findings reveal that the variables are cointegrated in the long-run and a 1% unit raise in energy consumption would trigger CO2 emissions by 0.46%. The increase in energy consumption in the long term affects both negatively and positively in the long term. While a 1% increase in energy consumption reduces carbon emissions by 0.48%, a 1% decrease causes a 0.35 decrease in carbon emissions. The positive increase in economic growth and the negative increase in energy consumption trigger environmental pollution by causing an increase in carbon dioxide emissions. There is interdependence between economic activities and environmental pollution. Policy makers need to adopt a strategic approach in solving the rapid industrialization phenomenon and the accompanying magnitude of energy consumption, the pressure on natural resources and the environmental pollution problems resulting from them. In this respect, it is an inevitable necessity for countries to continue multilateral negotiations in which the public sector, business world, academia and non-governmental organizations will take part in solving environmental problems.